The Influence of Family Support, Teaching Method, Peer, Gadget Usage on The Learning Motivation of Students of SD Islam Terpadu Ash Shiddiq (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
This research aims to identify the influence of family support, teaching method, peer, and gadget usage on the learning motivation of students of SD Islam Terpadu Ash Shidiqq. The type of this research is a survey with a quantitative approach. The population of this research was 60 student guardians recruited through a saturated sample and was done by the methods of questionnaire and documentation. Data were then analyzed using Structural Equation Model (SEM) assisted by the SmartPLS application. The research result put into evidence the influence of learning motivation. The following are the results sequenced from the lowest to the highest; family support with P-Values 0.000, gadget usage with a value of 0.010, peer with a value of 0.030, and teaching method with a value of 0.047. Based on the Goodness of Fit analysis of 0,696, R Square resulted in 0.900. This value showed that the used model predicted an excellent model. The implication of this research is that to increase students' learning motivation of SD IT Ash Shidqq, family support and gadget usage need to be handled better.